Coping Strategies among Employees towards Occupational Stress - Jessie Richie N. de los Santos; Ira G. Albasin; Michelle G. de los Santos (Health Notions, 2018)
Workplace, being a dynamic and changing environment is considered to be one of the major sources of daily stress among employees. Various researchers identified ways of coping to address the demand of occupational stress. Eastern Visayas State University – Tanauan Campus as an academic institution is expected to provide timely and responsive services to its stakeholders. The study sought to evaluate the relationship of coping strategies to level of occupational stress among employees of EVSUTC that will provide basis for possible implementation of health and wellness program or policy intervention in stress management program. The study was anchored on the Job Demand Control Model which provides explanation on the occupational stress level among employees. The study utilized a standardized instrument and questionnaires were distributed to 146 respondents to extract the different variables and its relationship. Descriptive-correlational design was also utilized and appropriate statistical treatment observed to obtain association. The study revealed employing selfefficacy (one’s own motivation) as the primary coping strategies identified to be effective in addressing stress. The findings also revealed, that new employees have higher stress level, while those with longer number of work or occupational experience display lesser amount of stress. The researchers recommend that university administrators should focus on faculty welfare by providing a health and wellness program to address occupational related – stress. Policy related to health promotion and prevention should also be considered. Senior employees are also encouraged to conduct mentoring and capacity training among junior personnel in order lessen the level of occupational stress. Keywords: Coping strategies, Occupational stress, University employees, Job demand control model